CLINICAL OUTCOMES OF COMPRESSION ALONG WITH ULTRASOUND GUIDED FOAM SCLEROTHERAPY IN THE MANAGEMENT OF VENOUS ULCERS: A PROSPECTIVE STUDY AT TERTIARY CARE HOSPITAL, PESHAWAR. : JPUMHS;2024:14:04,41-49. http://doi.org/10.46536/jpumhs/2024/14.04.559 - Shafi Ullah1, Ahmad Arsalan Tahir2, Muhammad Ishfaq3, Nasir Bakhtiar4, Ambareen Subhan5, Muhammad Farooq6. , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
ABSTRACT BACKGROUND: Ultrasound-guided foam sclerotherapy UGFS has been demonstrated to be as successful as open surgery in the management of venous ulcers. OBJECTIVE This study aimed to evaluate the clinical outcomes of compression along with ultrasound guided foam sclerotherapy in the management of venous ulcers. MATERIAL AND METHODS: This eighteen-month prospective observational study was conducted from July 2022 to December 2023 with a follow up period of one year at a Tertiary Care Hospital in Peshawar. Patients were recruited through non-probability convenience sampling. Prospective assessments were conducted on patients with superficial truncal venous incompetence and active venous leg ulcers CEAP clinical class C6 diagnosed through clinical evaluation and findings from doppler ultrasound. Baseline clinical, imaging, and demographic data were gathered before the the standard procedure of compression therapy and ultrasound guided foam sclerotherapy. The time frame from the intervention to the complete healing of the ulcer and the rate of ulcer recurrence throughout the one-year follow-up period were the main outcome measures RESULTS: The study included 33 individuals aged 40-50, with a mean age of 43 ± 5 years. The gender distribution was 19 men 57.6% and 14 women 42.4%. By the end of the one-year follow-up period, 26 patients 78.8% had fully healed ulcers, three patients 9.1% had incomplete healing, with ulcers showing moderate improvement but not fully healing. Four patients 12.1% had unhealed ulcers, indicating no progress during the research period. Ulcer recurrence was reported in one patient 4% who had previously healed ulcers. The healed ulcers had an average size reduction of 80% ± 5%. The average time for healing was 14 ± 3 weeksvCONCLUSION: The results of this study concluded that, treating venous ulcers with compression therapy and ultrasound-guided foam sclerotherapy together significantly improves healing rates, reduces ulcer size, and enhances patient quality of life. The beneficial result of this study encourages the use of this combination therapy strategy in clinical settings for improved patient care.